Effect of COVID19 pandemic and national lockdown on persons with diabetes from rural areas availing care in a tertiary care center, southern India. Issue 6 (November 2020) - Olickal, Jeby Jose; Chinnakali, Palanivel; Suryanarayana, B.S.; Ulaganeethi, Revathi; Kumar, Swetha S.; Saya, Ganesh Kumar
Abstract: Background and aims: COVID-19 pandemic and lockdown measures to contain it have affected health care services globally. This study aims to assess the effect and urban-rural differences of COVID19 pandemic on diabetes care. Methods: This cross-sectional study was conducted among persons with diabetes (PWDs) registered for care at a diabetes clinic of a tertiary care center in Southern India. We collected following information by telephonic interviews: physician consultations, access to diabetes medications and blood sugar tests, use of telemedicine services, out of pocket expenditure and psychological morbidity. Results: A total of 350 PWDs were interviewed. Majority were male (78%) and from rural areas (79%). One fourth (24%) met any physician for diabetes care at least once during lockdown. PWDs from rural areas mainly consulted a physician in a private clinic (55%) compared to urban areas (26%). Two third (65%) availed medications from private medical shops. Almost half (46%) got their blood sugar tested during and majority of them (81%) reported unsatisfactory glycemic control. Only few (5%) was aware and three utilized telemedicine services. Almost all (99%) spent money (US 8.3) for diabetes care. One third (33%) had moderate or high psychological distress. Conclusions: Majority of PWDs did not consult a physician during lockdown. Cost of care was high. Measures to improve utilisation of telemedicine services and peripheral health facilities are needed. Highlights: Only 24% of persons with diabetes (PWD) from rural areas met any physician for diabetes care during lockdown period. Most of them availed DM medications from private medical shops and only few were aware of telemedicine services. Almost all (99%) spent money (median US 8.3) for diabetes care during lock down. One third (33%) had moderate or high psychological distress.